2015
DOI: 10.1021/jacs.5b06657
|View full text |Cite
|
Sign up to set email alerts
|

Critical Factors Driving the High Volumetric Uptake of Methane in Cu3(btc)2

Abstract: A thorough experimental and computational study has been carried out to elucidate the mechanistic reasons for the high volumetric uptake of methane in the metal-organic framework Cu3(btc)2 (btc(3-) = 1,3,5-benzenetricarboxylate; HKUST-1). Methane adsorption data measured at several temperatures for Cu3(btc)2, and its isostructural analogue Cr3(btc)2, show that there is little difference in volumetric adsorption capacity when the metal center is changed. In situ neutron powder diffraction data obtained for both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
61
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(68 citation statements)
references
References 49 publications
(99 reference statements)
4
61
0
3
Order By: Relevance
“…In the past two decades, great endeavors have been dedicated to developing new MOF materials for high-capacity methane storage. [16][17][18][19][20][21][22][23][24] To date, the highest volumetric methane storage and working capacity for all reported MOFs at 65 bar and room temperature (RT) are about 270 and 200 cm 3 (STP) cm À3 , respectively. [25][26][27] Despite significant progress, there are still no MOF materials whose methane storage capacities can fulfill the new DOE targets at RT.…”
Section: The Bigger Picturementioning
confidence: 99%
“…In the past two decades, great endeavors have been dedicated to developing new MOF materials for high-capacity methane storage. [16][17][18][19][20][21][22][23][24] To date, the highest volumetric methane storage and working capacity for all reported MOFs at 65 bar and room temperature (RT) are about 270 and 200 cm 3 (STP) cm À3 , respectively. [25][26][27] Despite significant progress, there are still no MOF materials whose methane storage capacities can fulfill the new DOE targets at RT.…”
Section: The Bigger Picturementioning
confidence: 99%
“…As a benchmark of methane adsorption (200 cm 3 cm −3 at 80 bar, 298 K), HKUST‐1 shows its remarkable performance which could be an alternative material to traditional methane compression technology. HKUST‐1 was considered as the most hopeful CH 4 uptake material according to the research of Hulvey et al where they found the methane–methane interaction is the main factor explaining its enhanced bond at the copper metal sites …”
Section: Application Of the Hkust‐1 And Its Derivativesmentioning
confidence: 99%
“…Hulvey et al thought it was the interaction between methane molecules and not the electronic interaction resulting in the strong methane binding. It is useless to change the center metal atom when the structure did not change, which was proved by the adsorption data of replacing Cu 2+ with Cr 2+ . A recent research creatively succeeded in preparing a type of compact, flexible, and high hardness of HKUST‐1 and surprisingly found it had an outstanding methane adsorption uptake.…”
Section: Application Of the Hkust‐1 And Its Derivativesmentioning
confidence: 99%
“…The combination of experiments and calculations revealed that the high methane uptake and deliverable capacity of HKUST‐1 is mainly contributed to the CH 4 −CH 4 interactions with the effect of adsorbed compounds rather than its OMS . Such CH 4 −CH 4 interactions can be further amplified in the confinement space to increase the methane packing density in the pores and improve the methane storage performance.…”
Section: Milestones Of Mof Methane Adsorbentsmentioning
confidence: 99%